Strengthening Character Education Based on Al-Islam Kemuhammadiyahan Values through the ‘Ruang Hati Pagi’ Program in Elementary Schools: Penguatan Karakter Berbasis Nilai Al-Islam Kemuhammadiyahan melalui Program ‘Ruang Hati Pagi’ di Sekolah Dasar - Fahria Syamsudin; Dien Nurmarina Malik Fadjar (Jurnal Evaluasi dan Kajian Strategis Pendidikan Dasar, 2026)
This study examines the implementation of the “Ruang Hati Pagi” program as a daily morning routine to strengthen elementary students’ character through Al‑Islam Kemuhammadiyahan (AIK) values in a public-school setting. Using a descriptive qualitative design, the study was conducted at SD Negeri 13 Kota Sorong from early April to the first week of June 2025. Data were gathered through repeated participatory observations, semi‑structured interviews with the homeroom teacher and selected first‑grade students, and documentation (teacher notes, activity records, and students’ works). Data were analyzed using Miles and Huberman’s interactive model (data reduction, data display, and conclusion drawing/verification) and strengthened through triangulation, member checking, peer debriefing, and an audit trail. The findings show that the program is implemented consistently in four phases: (1) warm greeting and emotional check‑in, (2) morning sharing, (3) circle of kindness, and (4) reflective closing. These phases facilitate character internalization indicated by observable behaviors such as gratitude, respect, empathy/helping, honesty, responsibility, and improved self‑regulation. Implementation challenges include limited time allocation, uneven student participation, the need for teachers’ facilitation skills, and the necessity of parent–school collaboration to sustain values beyond the classroom. The novelty of this study lies in offering an operational micro‑routine model that integrates AIK values with SEL‑oriented classroom practices, along with measurable indicators of character internalization for early grades.